Toward a Biochemical Diagnosis of NASH: Insights From Pathophysiology For Distinguishing Simple Steatosis From Steatohepatitis - YILMAZ, YUSUF (BENTHAM SCIENCE PUBL LTD, 2011)
With the continuing epidemics of obesity and diabetes, nonalcoholic fatty liver disease (NAFLD) has received increased attention. Great efforts are being undertaken to improve the noninvasive diagnosis of NAFLD, with the ultimate goal of optimizing treatment options and clinical outcomes. Research suggests that blood-borne biochemical markers can be used to distinguish simple steatosis from nonalcoholic steatohepatitis (NASH), thus reducing the need of liver biopsy. Future developments in the field of diagnostic biochemistry within the spectrum of NAFLD can make this approach ideal for screening and monitoring purposes. In this review, we provide an overview of the different blood-borne markers which have been recently proposed for differentiating simple steatosis from NASH. We will also consider the practical and statistical issues that seem to be limiting the effective integration of biomarkers into clinical development.
Keywords: Nonalcoholic fatty liver disease; steatosis; steatohepatitis; biomarkers; FATTY LIVER-DISEASE; DIFFERENTIATE SIMPLE STEATOSIS; POLYPEPTIDE SPECIFIC ANTIGEN; NONALCOHOLIC STEATOHEPATITIS; INSULIN-RESISTANCE; CARDIOVASCULAR-DISEASE; THERAPEUTIC TARGET; METABOLIC SYNDROME; SOLUBLE RECEPTOR; NATURAL-HISTORY